2002
DOI: 10.1021/je020135f
|View full text |Cite
|
Sign up to set email alerts
|

Liquid−Liquid Equilibrium and Excess Enthalpies in Binary Systems Methylcyclohexane + Methanol and Methylcyclohexane + N,N-Dimethylformamide

Abstract: Liquid−liquid equilibrium and excess enthalpies were studied for the two binary systems:  methylcyclohexane + methanol and methylcyclohexane + N,N-dimethylformamide. Points of the binodal curve in the vicinity of the critical point were established in both of the systems by means of the cloud-point method. Equilibrium compositions were determined at different temperatures using the direct analytical method and the volume method. Excess enthalpies as functions of composition were determined at 298.15 K and 313.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…Recently, detailed measurements of binary LLE systems containing DMF and hydrocarbons were reported by Bendova et al [22,23]. Here, the authors measured the experimental LLE data for two binary systems: DMF + methylcyclohexane [22] and DMF + 2-methylpentane [23].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, detailed measurements of binary LLE systems containing DMF and hydrocarbons were reported by Bendova et al [22,23]. Here, the authors measured the experimental LLE data for two binary systems: DMF + methylcyclohexane [22] and DMF + 2-methylpentane [23].…”
Section: Introductionmentioning
confidence: 96%
“…Here, the authors measured the experimental LLE data for two binary systems: DMF + methylcyclohexane [22] and DMF + 2-methylpentane [23]. In a similar study, Lobos et al reported the cloud points for DMF + saturated hydrocarbon (C 6 -C 9 ) systems in the vicinity of the upper critical solution temperature (UCST) [24].…”
Section: Introductionmentioning
confidence: 99%
“…To study ternary systems N,N-dimethylformamide (1) + 2-methylpentane (2) + methanol (3) and N,N-dimethylformamide (1) + methylcyclohexane (2) + methanol (3) concentration series issuing from the subsystems (2) + (3) and (1) To measure solution temperatures, a cloud-point apparatus working on the principle of measurement of the intensity of the light scattered by the measured mixture as function of linearly decreasing temperature was used. The apparatus was described in a previous work [2]. The appearance or disappearance of the turbidity (second phase) caused by temperature change in the vicinity of critical points of systems N,N-DMF + methylcyclohexane and N,N-DMF + 2-methylpentane was not very apparent due to the iso-refractivity of liquid phases.…”
Section: Cloud-point Interpolation Methodsmentioning
confidence: 99%
“…Experimental liquid-liquid equilibrium data for binary systems methylcyclohexane + methanol, methylcyclohexane + N,N-dimethylformamide, and 2-methylpentane + N,N-dimethylformamide were already published [2,3], data for the system 2-methylpentane + methanol being equally available [4]. To describe the binary systems, the regular solution model was used:…”
Section: Theoreticalmentioning
confidence: 99%
See 1 more Smart Citation